Firms' rationales for CEO duality: Evidence from a mandatory disclosure regulation - Goergen, Marc; Limbach, Peter; Scholz-Daneshgari, Meik (Journal of Corporate Finance, 2020)
Exploiting the 2009 amendments to Regulation SK, we provide unique evidence on the first-time disclosure of the reasons firms state for combining or separating the roles of CEO and chairman. The stated reasons support both agency theory and organization theory. They are more numerous, comprise more words, and have a more positive tone for firms with duality. Examining the announcement returns to firms' disclosures, we find that investors evaluate the most frequently cited reasons for CEO duality by considering firm's characteristics. Our evidence enhances the understanding of firms' endogenous decision to opt for CEO duality and its value consequences.